2002
DOI: 10.1074/jbc.m109261200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Active and Inactive Conformations of a Caliciviral RNA-dependent RNA Polymerase

Abstract: The structure of the RNA-dependent RNA polymerase (RdRP) from the rabbit hemorrhagic disease virus has been determined by x-ray crystallography to a 2.5-Å resolution. The overall structure resembles a "right hand," as seen before in other polymerases, including the RdRPs of polio virus and hepatitis C virus. Two copies of the polymerase are present in the asymmetric unit of the crystal, revealing active and inactive conformations within the same crystal form. The fingers and palm domains form a relatively rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
152
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 39 publications
3
152
0
Order By: Relevance
“…The conformations adopted by the rabbit hemorrhagic disease virus polymerase can vary dramatically depending on the ions present in the crystallization solution. It was suggested that these structural changes may be important for the enzymatic activity of the protein (38). As reported previously for DNA polymerases (39,40), these conformational changes are probably required for the catalytic activity of rabbit hemorrhagic disease virus and HCV polymerases.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The conformations adopted by the rabbit hemorrhagic disease virus polymerase can vary dramatically depending on the ions present in the crystallization solution. It was suggested that these structural changes may be important for the enzymatic activity of the protein (38). As reported previously for DNA polymerases (39,40), these conformational changes are probably required for the catalytic activity of rabbit hemorrhagic disease virus and HCV polymerases.…”
Section: Discussionmentioning
confidence: 77%
“…In fact, comparisons with closely related polymerases strongly suggest that conformational changes are required for NS5B to efficiently initiate polymerization (28). However, analysis of the crystal structure the RNA polymerase of the rabbit hemorrhagic disease virus, a virus closely related to HCV, revealed the presence of both active and inactive conformations within the same crystal form (38). The conformations adopted by the rabbit hemorrhagic disease virus polymerase can vary dramatically depending on the ions present in the crystallization solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, representative RdRps from five families of RNA viruses have known three-dimensional structures: (1) Picornaviridae, poliovirus (Hansen et al, 1997;Thompson and Peersen, 2004;Thompson et al, 2007), human rhinovirus (Love et al, 2004), coxsackievirus (Campagnola et al, 2008), foot-and-mouth-disease virus (FMDV) (Ferrer-Orta et al, 2004); (2) Caliciviridae, rabbit hemorrhagic disease virus (Ng et al, 2002), Norwalk virus (Zamyatkin et al, 2008); (3) Flaviviridae, hepatitis C virus (Bressanelli et al, 1999;Lesburg et al, 1999), bovine viral diarrhea virus (Choi et al, 2006), Dengue virus (Yap et al, 2007), West Nile virus ; (4) Cystoviridae: phage f6 (Butcher et al, 2001;Salgado et al, 2004); and (5) Reoviridae, reovirus (Tao et al, 2002). The RdRp enzymes share a similar overall structure Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic structures of several viral RNA (vRNA)-dependent RNA polymerases from positive-and double-stranded RNA viruses are available (1)(2)(3)(4)(5)(6). These proteins show little sequence homology with other DNA-dependent polymerases but contain specific sequence motifs shared with other polymerases (7).…”
mentioning
confidence: 99%